Effect of Initial Oxygen Concentration on Diacetyl and Acetoin Production by Lactococcus lactis subsp. lactis biovar diacetylactis - Bassit, Naïma (1993)
The production of aroma compounds (acetoin and diacetyl) in fresh unripened cheese by Lactococcus lactis subsp. lactis biovar diacetylactis CNRZ 483 was studied at 30°C at different initial oxygen concentrations (0, 21, 50, and 100% of the medium saturation by oxygen). Regardless of the initial O(2) concentration, maximal production of these compounds was reached only after all the citrate was consumed. Diacetyl and acetoin production was 0.01 and 2.4 mM, respectively, at 0% oxygen. Maximum acetoin concentration reached 5.4 mM at 100% oxygen. Diacetyl production was increased by factors of 2, 6, and 18 at initial oxygen concentrations of 21, 50, and 100%, respectively. The diacetyl/acetoin concentration ratio increased linearly with initial oxygen concentration: it was eight times higher at 100% (3.3%) than at 0% oxygen (0.4%). The effect of oxygen on diacetyl and acetoin production was also shown with other lactococci. At 0% oxygen, specific activity of α-acetolactate synthetase (0.15 U/mg) and NADH oxidase (0.04 U/mg) was 3.6 and 5.4 times lower, respectively, than at 100% oxygen. The increasing α-acetolactate synthetase activity in the presence of oxygen would explain the higher production of diacetyl and acetoin. The NADH oxidase activity would replace the role of the lactate dehydrogenase, diacetyl reductase, and acetoin reductase in the reoxidation of NADH, allowing accumulation of these two aroma compounds.